The process of knowledge acquisition through interpersonal communication in the "Parents as first teachers" programme : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Communication Management at Massey University - Williams, Jocelyn Elizabeth (Massey University, 2001)
Communication researchers interested in the role played by knowledge in social terms have produced a variety of explorations in recent times of "knowledge gaps" and informational inequities between various groups in society. More broadly, studies of the significance of issues of relative access to information and thus ability to participate in civil society have been described as the sociology of knowledge. Arising out of an interest in documenting successful strategies in bridging knowledge gaps, the present study aimed to explore an information programme called Parents As First Teachers (PAFT), which operates on the basis of a one to-one relationship between informationally needy individuals (parents of newborn infants) and trained experts in parenting matters. This arrangement continues monthly for three years. It seemed likely that this information programme could present an example of an effective receiver-focused model of bridging knowledge gaps. A series of 22 in-depth interviews was conducted with parent and educator participants in the PAFT programme in Auckland, New Zealand. In addition, observation was carried out of the hour-long monthly home visits so that a detailed picture could be obtained of the significance of the interpersonal relationship between parent and educator for effective learning. Transcripts of interviews were analysed using a coding protocol developed on the basis of the research objectives. The study found limited support for the contentions of extant information poverty literature in regard to self-imposed isolation and avoiding disclosing problems. Interviewees preferred to isolate themselves within their neighbourhoods, but they did seek information via family and social networks. They were also highly motivated in regard to seeking the best for their children, and it is possible that motivation in this instance has been a more powerful factor in knowledge acquisition than education, often used as a predictor of response to informational need. The significance of this study is in its detailed presentation of the information world of the insider, and the support the data give for a situational approach to knowledge gaps. It signals that there is a definite role for a close and trusting interpersonal relationship between source and receiver in the knowledge acquisition process. Two key areas for follow-up studies are the role played by interpersonal communication networks in disseminating knowledge beyond the original knowledge exchange context, and whether the strong motivation observed in the parents interviewed for this research was attributable to the PAFT programme itself or was a characteristic already present in participants.
Keywords: Interpersonal communication; Parents First Teachers (Program); Knowledge, Sociology of; Communication; New Zealand